Comparative evaluation of the Bruker Biotyper and Vitek MS matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry systems for identification of yeasts of medical importance - Mancini, Nicasio; De Carolis, Elena; Infurnari, Laura; Vella, Antonietta; Clementi, Nicola; Vaccaro, Luisa; Ruggeri, Alberto; Posteraro, Brunella; Burioni, Roberto; Clementi, Massimo; Sanguinetti, Maurizio (Journal of clinical microbiology, 2013)
We report the first comparative evaluation between the Bruker Biotyper MS (BMS) and the Vitek MS (VMS) for the identification of yeasts. The rate of correct identifications at the species level was comparable using the commercial databases (89.8% versus 84.3%; P = 0.712), but higher for BMS using an in-house-extended database (100% versus 84.3%; P = 0.245). Importantly, the rate of misidentification was significantly higher for VMS (1% versus 12.1%; P < 0.0001), including the rate of major errors (0% versus 4.5%; P = 0.0036).